Bloody coli: a Gene Cocktail in Escherichia coli O104:H4 - Fernando Baquero (American Society for Microbiology, 2013)
ABSTRACT A recent study published in mBio [Y. H. Grad et al., mBio 4(1):e00452-12, 2013] indicates that a rapid introgressive evolution has occurred in Escherichia coli O104:H4 by sequential acquisition of foreign genetic material involving pathogenicity traits. O104 genetic promiscuity cannot be readily explained by high population sizes. However, extensive interactions leading to cumulative assemblies of pathogenicity genes might be assured by small K-strategist populations exploiting particular intestinal niches. Next-generation sequencing technologies will be critical to detect particular “gene cocktails” as potentially pathogenic ensembles and to predict the risk of future outbreaks.